Institutional Capacity in the Mangrove Ecotourism Development of Lembar Area, West Lombok, Indonesia - Sukuryadi Sukuryadi; Harry Irawan Johari; Mimit Primyastanto; Bambang Semedi (Faculty of Fisheries and Marine Science, Brawijaya University, 2021)
Mangrove ecotourism development with an institutional approach aims to carry out management by uniting relevant institutions especially the community, government, and other stakeholders. Institutional capacity plays an important role in the development of potential-based areas. Therefore, this study aims to determine institutional capacity both organizational and individual capacity in the mangrove ecotourism development in the Lembar village of Lombok Barat Regency. The research method was carried out through a qualitative research approach with the determination of informants based on purposive sampling techniques. The results showed that the capacity of mangrove ecosystem management for the mangrove ecotourism development in the Lembar village area of West Lombok Regency at the level of community, individual resource managers and institutional was categorized as low. The dominant institutional capacity in the mangrove ecotourism development were the Marine and Fisheries Department of West Lombok Regency. This shows that good synergy has not yet been formed between institutions and communities so that the mangrove ecotourism development is unsustainable and temporal. Therefore, a joint commitment is needed in increasing the strengthening of institutional capacity sustainably so that there is good synergy between the government, the government and the private sector, the government and the community, and between other stakeholders.